AB0520 Evaluating the Effect of Belimumab on Clinical Disease Activity and B-Cell in Patients with Systemic Lupus Erythematosus. (9th June 2015) - Hernandez-Flόrez, D.; Valor, L.; del Río, T.; Nieto, J.C.; Martinez, J.; Ovalles, J.; Gonzalez, C.; Lόpez-Longo, F.J.; Monteagudo, I.; Naredo, E.; Carreño, L.
Abstract : Background: Systemic lupus erythematosus (SLE) is an autoimmune inflammatory disease with wide ranging multi-systemic effects and clinical manifestations of fluctuating intensity and severity (1). This is characterized by dysfunction of T-cells and B-cell (BC) activation and an abnormal production of autoantibodies (2). Anomalous patterns in the expression of pro-inflammatory and anti-inflammatory cytokines and soluble proteins concentration such as sBAFF (B- soluble cell activating factor) has been described. Belimumab is a fully humanised monoclonal antibody against BAFF for use in combination with standard immunosuppressants in autoantibody-positive SLE (3). Objectives: To evaluate the impact of belimumab on disease activity, serological and phenotypical B-cell markers in SLE patients. Methods: Eight patients diagnosed with SLE and treated with belimumab were assessed clinical, serological and phenotypically at baseline, 4 and 8 months. Disease activity was evaluated using the SLEDAI score (Systemic Lupus Erythematosus Disease Activity Index). Remission was defined as SLEDAI<3, moderate disease activity as SLEDAI=3-12 and severe disease activity as SLEDAI>12. sBAFF, TNF-alpha and IL-17A serum levels were determined by ELISA. BC phenotyping was performed using multiparameter flow cytometry. A control group was evaluated to compare serological and phenotypical variables. Results: We found a progressively decreased disease activity measured by SLEDAI, absolute BC-CD19+ count and anti-DNA antibodies, whereas the platelet count increased progressively. Regarding sBAFF, TNF-alpha and IL-17A serum levels, these were persistently elevated in the SLE group compared to the control group. Furthermore, sBAFF serum levels increased while IL-17A and TNF-alpha decreased during follow up in the SLE group. We observed changes on BC phenotype in the SLE group when comparing with controls. In the SLE group, we observed a decrease in percentages (%) of BC- naïve (CD19+/CD27-) and an increase in % of BC-memory (CD19+/CD27+). Respect to BC subsets, we observed a decrease in the % of BC-naïve-mature (CD19+IgD+CD38+) and plasmablasts (CD19+IgD-CD38++), and an increase in BC-post-germinal-center (CD19+IgD-CD38+) and BC-memory-resting (CD19+/IgD+/CD38-). We found an inverse correlation of SLEDAI with both haemoglobin and C3 (p=0.046, p=0.01, respectively). Conclusions: Our results suggest that the response to belimumab in SLE patients might be associated with both a decrease in the percentages of BC- naïve and a progressive increase of sBAFF serum levels. These observations may be a potential indicator of therapeutic response, and these findings should be corroborated in larger cohorts and longer follow-ups. References: Kamal A, Khamashta M.Autoimmun Rev. 2014 Nov;13(11):1094-101. Liossis SN, Melissaropoulos K. Expert Opin Pharmacother. 2014 Apr;15(6):833-40. Lutalo PM, D'Cruz DP. Expert Opin Biol Ther. 2014 Nov;14(11):1701-8. Disclosure of Interest: None declared